Crude oil price: Demand, supply, economic activity, economic policy uncertainty and wars: from the perspective of structural equation modelling (SEM) - Wang, Qingfeng; Sun, Xu (Elsevier, 2017)
We studied the relationship between the change in the price of oil and some of its determinants, using a structural equation model. The demand for oil is confirmed to be inelastic to the change in oil price during our sampling period. Economic activity is found to be the most significant factor in explaining the dynamics of oil price. Wars and political tension, among the largest oil producers and their neighbouring countries, can drive the crude oil price sharply higher, but no significant direct effect was confirmed by the SEM. The significant effects of wars and political tension on the price of oil lies in their ability to disrupt oil supplies.